Исследование оптических сигналов методами топологической фотоники - Пуляев, Ю. С. (ХНУРЕ, 2019)
The paper presents a topological model for the search and identification of hidden optical surveillance systems. The model is based on fractal ideas about the structure of the optical signal and the determination of the fractal dimension of the intensity distribution in the section plane of a laser pulse reflected from the target. A wide range of information security tasks, maintaining commercial secrets, includes the task of protecting against unauthorized video and photographing